Sistem Pakar Pengembangan Kualitas SDM Di Gunungrejo Pada Bidang Ekonomi Menggunakan Metode Certainty Factor - Alwan Aziz (Journal of Information System and Artificial Intelligence, 2024)
The development of the quality of human resources is very important for us to develop because there are still many people out there who have difficulty living their daily lives. Moreover, to get a decent economic needs. Therefore, we discuss the development of the quality of Human Resources in the economic field. So that the layers of society can meet decent economic needs. The method used to develop the quality of Human Resources, with the Certainty Factor method. Certainty Factor method, in this study is used to assist in overcoming economic problems with the aim of improving the quality of human resources in Indonesia. From the results of testing the expert system program, in the research results obtained various problem conditions that determine whether a person has a quality deficiency in the economic field. With the creation of this journal, it is hoped that it can help to improve the quality of Human Resources appropriately.